REFLEKSIFITAS METODE FREE DISCOVERY LEARNING - Rifqi, Naflah (Muta'allim: Jurnal Pendidikan Agama Islam, 2023)
Multidimensional PAI learning requires a strategic method. With short portions, 3 hours of lessons the teacher must be good at combining teaching methods that are able to improve students' cognitive, affective and psychomotor competencies. The demands of digitization, an independent curriculum and the characteristics of the Z-generation that always require innovation are joint homework. One solution is discovery learning. The author raises one of its branches, namely Free Discovery learning, which is synonymous with student-centered. Starting from planning, processing and learning direction is determined independently by students. This study aims to test whether FDL (Free Discovery learning) can cover the many demands of PAI learning above with reflexivity, weaknesses and strengths from cognitive, affective and psychomotor aspects. The author uses a qualitative descriptive method with questionnaire data collection techniques and pre-test post-test. The results of FDL in class IX PAI Islamic Middle School Sunan Giri showed a prominent increase in terms of affective, then psychomotor and a slight increase in cognitive. Some of the factors that most influence this are teacher competence, short lesson hours and the non-linearity of student presentation material with cognitive tests conducted by the teacher. Abstrak Pembelajaran PAI yang multidimensional memerlukan metode strategis. Dengan porsi singkat yakni 3 jam pelajaran dalam satu pekan, maka guru harus pandai mengkombinasikan metode ajar yang mampu meningkatkan kompetensi kognitif, afektif, dan psikomotorik siswa. Tuntutan digitalisasi, kurikukum merdeka dan karakteristik generasi-Z yang selalu membutuhkan inovasi menjadi PR bersama. Salah satu solusinya adalah discovery learning. Penulis mengangkat satu cabangnya yakni Free Discovery learning, yang identic dengan student-centered learning. Mulai dari perencanaan, pengolahaan dan arah belajarnya ditentukan mandiri oleh siswa. Penelitian ini bertujuan menguji apakah FDL (Free Discovery learning) dapat meng-cover banyaknya tuntutan pembelajaran PAI di atas dengan refleksifitas (kelemahan dan kelebihan) berdasar aspek koginitf, afektif dan psikomotorik. Penulis menggunakan metode deskriptif kualitatif dengan teknik pengumpulan data questioner dan pre-test post-test. Hasil dari FDL pada pembelajaran PAI kelas IX SMP Islam Sunan Giri menunjukkan adanya peningkatan yang menonjol dari segi afektif dan psikomotor, namun sayangnya hanya sedikit peningkatan pada segi kognitif. Beberapa faktor yang paling mempengaruhi hal tersebut adalah kompetensi guru, jam pelajaran yang singkat dan ketidak linieran materi presentasi siswa dengan uji kognitif yang dilakukan guru.